Doing without concepts - Machery, Edouard (OUP E-Books., 2009)
In this work, Edouard Machery argues that the dominant psychological theories of concepts fail to provide a framework and that drastic conceptual changes are required to make sense of the research on concepts in psychology and neuropsychology.